Integrative Analyses of Transcriptomics and Metabolomics in Immune Response of Leguminivora glycinivorella Mats to Beauveria bassiana Infection - Hongqiang Fei; Juan Cui; Shiyu Zhu; Ye Xia; Yichang Xing; Yu Gao; Shusen Shi (Insects, 2024)
This study utilized Beauveria bassiana to infect Leguminivora glycinivorella, analyzed the effects on the transcriptome and metabolome, and further investigated the antibacterial function of L. glycinivorella. We performed transcriptome and metabolome sequencing on the L. glycinivorella infected with B. bassiana and its control groups, and performed a joint analysis of transcriptome and metabolome results. Upon screening, 4560 differentially expressed genes were obtained in the transcriptome and 71 differentially expressed metabolites were obtained in the metabolome. On this basis, further integration of the use of transcriptomics and metabonomics combined an analysis of common enrichments of pathways of which there were three. They were glutathione S-transferase (GSTs) genes, heat shock protein (HSP) genes, and cytochrome P450 (CYP450) genes. These three pathways regulate the transport proteins, such as ppars, and thus affect the digestion and absorption of sugars and fats, thus regulating the development of pests. The above conclusion indicates that B. bassiana can affect the sugar metabolism, lipid metabolism, and amino acid metabolism pathways of L. glycinivorella, and can consume the necessary energy, protein, and lipids of L. glycinivorella. The research on the immune response mechanism of pests against pathogens can provide an important scientific basis and target for the development of immunosuppressants. This study laid an information foundation for the application of entomogenous fungi to control soybean borer at the molecular level.